2018
DOI: 10.1002/admi.201801627
|View full text |Cite
|
Sign up to set email alerts
|

Sputter Depth‐Profile Study of Accelerated Interface Mixing by Thermal Annealing in Solution‐Processed Organic Light‐Emitting Diodes

Abstract: The effect of thermal annealing on interfacial mixing of solution‐processed organic light‐emitting diodes (OLEDs) using direct sputter‐depth profiling techniques is investigated. X‐ray and ultraviolet photoelectron spectroscopy and argon gas cluster ion beam sputtering are used to investigate the distribution of chemical species near the interface. Extensive interfacial mixing is found in solution‐processed OLEDs after the thermal annealing at temperatures below the glass transition temperature of the organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…[ 18 ] Lee et al observed that the HOMO onset moved toward lower BE gradual as sputtering prolonged on tris(4‐carbazoyl‐9‐ylphenyl)amine/crosslinkable‐hole transport material (TCTA/x‐HTM) film, which was also explained by the diffusion of the constitutive materials during the solution/annealing process. [ 19 ] Both groups claimed that the diffusions are absent in the case of vacuum deposition process. To investigate whether the diffusion occurs in our samples, a more refined sputtering processing (60 s for each sputtering interval) is performed, and no obvious difference of C and O elemental distribution can be observed between Alq 3 /NPB or NPB/Alq 3 interfaces (see in Figure S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 18 ] Lee et al observed that the HOMO onset moved toward lower BE gradual as sputtering prolonged on tris(4‐carbazoyl‐9‐ylphenyl)amine/crosslinkable‐hole transport material (TCTA/x‐HTM) film, which was also explained by the diffusion of the constitutive materials during the solution/annealing process. [ 19 ] Both groups claimed that the diffusions are absent in the case of vacuum deposition process. To investigate whether the diffusion occurs in our samples, a more refined sputtering processing (60 s for each sputtering interval) is performed, and no obvious difference of C and O elemental distribution can be observed between Alq 3 /NPB or NPB/Alq 3 interfaces (see in Figure S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] However, recent studies argued that the thermal annealing process to remove the residual solvent in solutionprocessed OLEDs induces intermixing at organic-organic (O-O) interfaces and enhances the device performance. [10][11][12][13][14] They employed either neutron reflectometry (NR) or time-offlight secondary ion mass spectroscopy (ToF-SIMS) to obtain the depth profiles of O-O interfaces. In particular, NR offered a quantitative evaluation of the composition of O-O interfaces in angstrom-ordered resolution and revealed that the onset temperature of thermal diffusion at O-O corresponds to the glass transition temperature (T g ) of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Based on such depth profile measurements, several studies asserted that the intermixing at the HTL/EML interface improved current injection or suppressed triplet polaron quenching and thereby enhanced the device performance. 11,14 However, those performance enhancements might predominantly be due to the thermally modified morphologies of organic layers rather than interface mixing. For example, several studies demonstrated that the thermal annealing process can orient transition dipole moments in the plane of a solution-processed EML, which can improve either current injection or the outcoupling efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Vacuum thermal evaporation and solution process are the two main technologies for the fabrication of OLEDs [ 8 ]. Compared with the vacuum evaporation process, the solution process is easier in terms of adjusting the proportion of host and guest materials in the doping system and is superior in large-scale production [ 9 , 10 , 11 , 12 , 13 ]. However, it is difficult to achieve efficient multi-stacked structures due to miscibility between organic layer interfaces in solution-processed devices and the wide band gaps (~3 eV) of phosphorescent materials which result in inferior hole injection.…”
Section: Introductionmentioning
confidence: 99%